An Exploration of Factors Affecting Work Anomia - Tsahuridu, Eva E. (2011)
Anomie, a societal and anomia an individual characteristic is employed to understand the behaviour of people and more recently it has been used to explore and understand the moral behaviour of people at work. This article reports on research undertaken to explore the relationship between organisational interest, ethical ideologies, employment, religion and ethnic origin on work and nonwork anomia. An objective of this research was to ascertain whether participants that were not employed had lower levels of work-related anomia than those that were employed. The sample consisted of students (N = 209) enroled in management degrees in a UK university. Results indicate that overall work anomia was statistically significant higher than nonwork anomia. Employment status had a significant effect on levels of nonwork anomia. Religion and ethnic origin were also found to have a significant effect on anomia levels. The findings indicate that the work context may be perceived as inherently anomic and this perception is then adjusted according to the actual experience at work. This may influence ethical behaviour and explain the ethical regression that is identified in the work context.
Keywords: Ethical Behaviour; Business Ethics; Anomia; Anomie